Firm Perceptions in Post-Revolutionary Tunisia - Issa, Djibrilla Adamou (World Bank, Washington, DC, 2014)
Through steady structural reforms and good macroeconomic management, Tunisia has been successful in sustaining growth. The country enjoyed a 4.8 percentage average annual growth in Gross Domestic Product (GDP) over most of the 2000`s, placing the country among the leading performers in the region. Most of the growth was driven by private enterprises in the export sectors. Tunisia did better than most countries in the region because it started structural reforms earlier and stayed the course in a gradual fashion. But many emerging countries, such as Malaysia and Turkey, which share similar growth models, outperformed Tunisia.